Decreased Expression of Thyroglobulin and Sodium Iodide Symporter Genes in Hashimoto's Thyroiditis. (4th March 2014) - Popławska-Kita, Anna; Telejko, Beata; Siewko, Katarzyna; Kościuszko-Zdrodowska, Maria; Wawrusewicz-Kurylonek, Natalia; Krętowski, Adam; Hryniewicka, Justyna; Dzięcioł, Janusz; Bauer, Witold; Milewski, Robert; Szelachowska, Małgorzata; Górska, Maria
Abstract : Aim . The aim of the study was to compare the expression of sodium iodide symporter (NIS), thyroglobulin (Tg), tumor necrosis factor- α (TNF α ), and interleukin-1 β genes in patients with Hashimoto's thyroiditis (HT) and healthy individuals. Subjects and Methods. Thyroid cells were obtained from 39 patients with HT and 15 controls by an ultrasound guided fine needle aspiration biopsy. Results . The patients with HT had lower Tg and NIS mRNA (P = 0.002 and P = 0.001, resp.), as well as higher TNF α mRNA expression (P = 0.049 ) than the controls. In the HT group Tg mRNA expression correlated positively with NIS mRNA expression (R = 0.739, P = 0.0001 ) and thyroid volume (R = 0.465, P = 0.0005 ), as well as negatively with TNF α mRNA expression (R = - 0.490, P = 0.001 ) and anti-peroxidase antibodies (TPOAb) level (R = - 0.482, P = 0.0002 ), whereas NIS mRNA expression correlated positively with thyroid volume (R = 0.319, P = 0.02 ), as well as negatively with TNF α mRNA expression (R = - 0.529, P = 0.0006 ) and TPOAb level (R = - 0.422, P = 0.001 ). Conclusions. Our results suggest that decreased Tg and NIS expression in thyroid cells may result in reduced active iodide transport and reduced thyroid volume in patients with HT.